Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fneur.2023.1221161
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Off-label use of low-dose perampanel in a 25-month-old girl with a pathogenic SYNGAP1 variant

Siddharth Gupta,
Yun Hwang,
Natasha Ludwig
et al.

Abstract: IntroductionPreclinical studies in a mouse model have shown that SYNGAP1 haploinsufficiency results in an epilepsy phenotype with excessive GluA2-AMPA insertion specifically on the soma of fast-spiking parvalbumin-positive interneurons associated with significant dysfunction of cortical gamma homeostasis that was rescued by perampanel (PER), an AMPA receptor blocker. In this single case, we aimed to investigate the presence of dysregulated cortical gamma in a toddler with a pathogenic SYNGAP1 variant and repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Given that AMPA receptors are a key mediator of glutamatergic neurotransmission involved in many functions, the AMPAr antagonist, perampanel (originally approved as an anti-seizure medication), has been used in a wide variety non-epilepsy or epilepsy associated conditions, including in autism with associated epilepsy ( 146 ). Several studies have looked at the efficacy of perampanel in rare epilepsies, including epilepsy associated with SYNGAP1-DEE ( 147 149 ). One study focused on rare epilepsy, which often feature significant developmental phenotypes, and revealed high efficacy for perampanel ( 148 ).…”
Section: Autism Associated With Prenatal Anti-seizure Medication Expo...mentioning
confidence: 99%
See 3 more Smart Citations
“…Given that AMPA receptors are a key mediator of glutamatergic neurotransmission involved in many functions, the AMPAr antagonist, perampanel (originally approved as an anti-seizure medication), has been used in a wide variety non-epilepsy or epilepsy associated conditions, including in autism with associated epilepsy ( 146 ). Several studies have looked at the efficacy of perampanel in rare epilepsies, including epilepsy associated with SYNGAP1-DEE ( 147 149 ). One study focused on rare epilepsy, which often feature significant developmental phenotypes, and revealed high efficacy for perampanel ( 148 ).…”
Section: Autism Associated With Prenatal Anti-seizure Medication Expo...mentioning
confidence: 99%
“…One study focused on rare epilepsy, which often feature significant developmental phenotypes, and revealed high efficacy for perampanel ( 148 ). Two more-focused studies (one a small case series the other a case report) evaluated the impact of perampanel on behavior in autism with associated epilepsy ( 147 , 149 ). The case series revealed that 7 out of 17 patients showed improvement on autism behavioral assessments, including two out of five patients that did not show reductions in seizures ( 149 ).…”
Section: Autism Associated With Prenatal Anti-seizure Medication Expo...mentioning
confidence: 99%
See 2 more Smart Citations